Understanding the effect of international remittances on undernourishment in Sub-Saharan Africa: A spatial model approach - (:unkn) unknown (My University, 2018)
This paper investigates the impact of remittances on undernourishment in Sub-Saharan Africa using panel data from 35 countries spanning the years 2001-2011. The panel Spatial Error Model (SEM) was used after taking into account the spatial interaction between countries. We find that remittances contribute to the reduction of undernourishment in Sub-Saharan African. However, the elasticity of calorie consumption to remittances is narrow. Moreover, the impact of remittances is more pronounced in intermediate income deciles countries than in the countries in lower income deciles and higher income deciles. Abstract This paper investigates the impact of remittances on undernourishment in Sub-Saharan Africa using panel data from 35 countries spanning the years 2001-2011. The panel Spatial Error Model (SEM) was used after taking into account the spatial interaction between countries. We find that remittances contribute to the reduction of undernourishment in Sub-Saharan African. However, the elasticity of calorie consumption to remittances is narrow. Moreover, the impact of remittances is more pronounced in intermediate income deciles countries than in the countries in lower income deciles and higher income deciles.
Keywords: African Research